2017
DOI: 10.1152/ajpgi.00157.2017
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of postprandial plasma bile acid kinetics in human volunteers

Abstract: Bile acids (BA) are signaling molecules with a wide range of biological effects, also identified among the most responsive plasma metabolites in the postprandial state. We here describe this response to different dietary challenges and report on key determinants linked to its interindividual variability. Healthy men and women ( = 72, 62 ± 8 yr, mean ± SE) were enrolled into a 12-wk weight loss intervention. All subjects underwent an oral glucose tolerance test and a mixed-meal tolerance test before and after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 66 publications
4
33
1
2
Order By: Relevance
“…Although the diurnal changes in C4 were more discrete on day 1 of the present study, they are comparable to those previously reported . As expected , levels of BAs, C4 and FGF19 showed considerable interindividual variation, but the patterns observed were consistent (Figure A‐C).…”
Section: Resultssupporting
confidence: 91%
“…Although the diurnal changes in C4 were more discrete on day 1 of the present study, they are comparable to those previously reported . As expected , levels of BAs, C4 and FGF19 showed considerable interindividual variation, but the patterns observed were consistent (Figure A‐C).…”
Section: Resultssupporting
confidence: 91%
“…BA absorption starts already in the duodenojejunum, with at least 25% of CDCA and DCA conjugates being reabsorbed in that segment, 40 presumably by passive diffusion and via OATP3. 41 An analysis by Fiamoncini et al 35 showed that variability in OATP3 expression may contribute to variability in postprandial plasma BA dynamics, whereas our analysis showed a small impact of duodenojejunal variability on daily average plasma BA levels. This may point to a compensatory increase in ileal BA absorption, preventing BA pool reduction, as detected by delayed BA absorption.…”
Section: Discussioncontrasting
confidence: 52%
“…9 This multifactorial nature of systemic plasma BA measurements complicates the identification of key factors that regulate BA pool distribution and composition. In their recent work, Fiamoncini et al 35 addressed this question by using a mixed-design analysis of a variance model exploiting host genome and microbiota data, in addition to systemic plasma BA profiles. However, interindividual variability is determined not only genetically, numerous additional factors, environmental and physiological, may contribute to the variability in BA pool size and composition.…”
Section: Discussionmentioning
confidence: 99%
“…The 13 most abundant bile acids in plasma were quantified with an adaptation of the method described by Tagliacozzi et al (28). In brief, 10 ml plasma was mixed with deuterated internal standards and, after methanolic extraction, the samples were injected into the LC-MS/MS system, as described in Fiamoncini et al (29).…”
Section: Plasma Metabolite Profilingmentioning
confidence: 99%